2013
DOI: 10.1186/1751-0147-55-30
|View full text |Cite
|
Sign up to set email alerts
|

Herd specific risk factors for Mycoplasma hyopneumoniae infections in suckling pigs at the age of weaning

Abstract: BackgroundMycoplasma hyopneumoniae is the etiologic agent of enzootic pneumonia mainly occurring in fattening pigs. It is assumed that horizontal transmission of the pathogen during nursery and growing phase starts with few suckling pigs vertically infected by the sow. The aim of the present study was the exploration of the herd prevalence of M. hyopneumoniae infections in suckling pigs followed by an investigation of various herd specific factors for their potential of influencing the occurrence of this patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 13 publications
1
28
3
1
Order By: Relevance
“…This observation regarding gilt acclimatisation was further confirmed by the results of the regression analysis, where the acclimatisation of gilts was the most important risk factor for a high ‘disease severity score’ among suckling, growing and finishing pigs. Similar importance of gilts for the course of the infection has been described in other studies determining the prevalence of M. hyopneumoniae in suckling pigs and corresponding risk factors, respectively [27, 37]. The hypothesis of young breeding animals being the main source of shedding of M. hyopneumoniae in sow herds is underlined by the observation that prevalence of the infection is significantly higher in those herds, where no acclimatisation for replacement boars (i.e.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This observation regarding gilt acclimatisation was further confirmed by the results of the regression analysis, where the acclimatisation of gilts was the most important risk factor for a high ‘disease severity score’ among suckling, growing and finishing pigs. Similar importance of gilts for the course of the infection has been described in other studies determining the prevalence of M. hyopneumoniae in suckling pigs and corresponding risk factors, respectively [27, 37]. The hypothesis of young breeding animals being the main source of shedding of M. hyopneumoniae in sow herds is underlined by the observation that prevalence of the infection is significantly higher in those herds, where no acclimatisation for replacement boars (i.e.…”
Section: Discussionsupporting
confidence: 70%
“…The likelihood of transmission of M. hyopneumoniae from sows to their offspring increased exponentially with the length of the suckling period, which is equal to the time under exposure [22, 26, 27]. Two scenarios assuming a length of the suckling period equal to 21 and 28 days, respectively, were tested.…”
Section: Methodsmentioning
confidence: 99%
“…Noteworthy, in one study describing the course of infection from birth to slaughter, a well comparable detection rate of 3.8% was found in suckling pigs at the age of weaning [14]. Moreover, a recent randomized cross-sectional study reported an overall detection rate of 3.9% in this particular age group [24]. Notwithstanding, the detection rate assessed with PCR on nasal swabs can be influenced by the virulence of the strain (i.e.…”
Section: Discussionmentioning
confidence: 94%
“…One explanation for the lower TI 200 in longer farrowing rhythms might be that a longer period in-between two batches guarantees a better separation between the age groups and allows for more cleaning and disinfection time, resulting in less risk of transmission of pathogens between them. For example Nathues et al [42] showed that piglets within a herd with a 3-week system were less likely to be infected with Mycoplasma hyopneumoniae compared to a 2-week system. His findings did not hold true for a 4-week system, but more pathogens and factors most likely influence our finding and not only M. hyopneumoniae , resulting in a positive effect in general for the longer farrowing rhythms.…”
Section: Discussionmentioning
confidence: 99%